Allometry of behavior and niche differentiation among congeneric African antelopes. Issue 1 (22nd September 2022) - Daskin, Joshua H.; Becker, Justine A.; Kartzinel, Tyler R.; Potter, Arjun B.; Walker, Reena H.; Eriksson, Fredrik A. A.; Buoncore, Courtney; Getraer, Alexander; Long, Ryan A.; Pringle, Robert M.
Abstract: Size‐structured differences in resource use stabilize species coexistence in animal communities, but what behavioral mechanisms underpin these niche differences? Behavior is constrained by morphological and physiological traits that scale allometrically with body size, yet the degree to which behaviors exhibit allometric scaling remains unclear; empirical datasets often encompass broad variation in environmental context and phylogenetic history, which complicates the detection and interpretation of scaling relationships between size and behavior. We studied the movement and foraging behaviors of three sympatric, congeneric spiral‐horned antelope species ( Tragelaphus spp.) that differ in body mass—bushbuck (26–40 kg), nyala (57–83 kg), and kudu (80–142 kg)—in an African savanna ecosystem where (i) food was patchily distributed due to ecosystem engineering by fungus‐farming termites and (ii) predation risk was low due to the extirpation of several large carnivores. Because foraging behavior is directly linked to traits that scale allometrically with size (e.g., metabolic rate, locomotion), we hypothesized that habitat use and diet selection would likewise exhibit nonlinear scaling relationships. All three antelope species selected habitat near termitaria, which are hotspots of abundant, high‐quality forage. Experimental removal of forage from termite mounds sharply reduced use of those mounds by bushbuck, confirming that habitat selection was resource driven. Strength of selection for termite mounds scaled negatively and nonlinearly with body mass, as did recursion (frequency with which individuals revisited locations), whereas home‐range area and mean step length scaled positively and nonlinearly with body mass. All species disproportionately ate mound‐associated plant taxa; nonetheless, forage selectivity and dietary composition, richness, and quality all differed among species, reflecting the partitioning of shared food resources. Dietary protein exhibited the theoretically predicted negative allometric relationship with body mass, whereas digestible‐energy content scaled positively. Our results demonstrate cryptic size‐based separation along spatial and dietary niche axes—despite superficial similarities among species—consistent with the idea that body‐size differentiation is driven by selection for divergent resource‐acquisition strategies, which in turn underpin coexistence. Foraging and space‐use behaviors were nonlinearly related to body mass, supporting the hypothesis that behavior scales allometrically with size. However, explaining the variable functional forms of these relationships is a challenge for future research.